(untitled) (Research, Society and Development, 2021)
Purpose: To develop and validate the content of the “Tempo de Tela’’ instrument for parents and/or guardians of children in the preschool period. Methods: 5 experts in the area of interest were selected to judge the instrument to be validated through a form with 12 dichotomous questions. The descriptive analysis was performed by calculating the simple frequency and content analysis was performed for the essay answers. Results: 100% of the judges judged the approach to the theme, direction to the content, clarity, coherence and cohesion, distribution of the questions and visual aspect as appropriate items. The changes considered were: adding a question (40%) and proposals for aesthetic changes (40%). Among the suggestions for adding questions are: The child’s educational level; if you study in a public or private school; parents’ socioeconomic level; parents’ perception of screen time. Regarding aesthetic changes, the following were mentioned: greater space for open questions; greater space between one question and another; alignment in the middle of the topic sentences; use Likert scale; keep the same question on a single page. Conclusion: The instrument was subjected to the content validation steps recommended in the literature and fulfills the requirements regarding its face and content.